Utilizing metagenomic next-generation sequencing to diagnose central nervous system infections after craniotomy - Wang, Jin; Jiang, Bingjie (The Journal of Infection in Developing Countries, 2026)
Introduction: Postoperative central nervous system (CNS) infections in craniotomy patients diagnosed through clinical signs and cerebrospinal fluid (CSF) bacterial culture, pose a challenge due to the morbidity and mortality of bacterial meningitis. The objective of this study was to evaluate the clinical value of metagenomic next-generation sequencing (mNGS) in diagnosing CNS infections post craniotomy. Methodology: A prospective study compared mNGS with traditional diagnostics from January 2021 to October 2023. Patients with suspected post-craniotomy intracranial infections were enrolled, following guidelines and regulations. Results: mNGS and traditional culture diagnosed 111 patients with suspected intracranial infections. mNGS showed higher sensitivity (62.5% vs. 25%). Traditional culture excelled in specificity and positive predictive value. Of the 18 mNGS-positive samples, 12 were culture-negative. mNGS detected pathogens such as Candida albicans (2 cases), Enterobacter cloacae (1 case), Enterococcus faecalis (1 case), Klebsiella pneumoniae (2 cases), Pseudomonas aeruginosa (1 case), Staphylococcus aureus (2 cases), Staphylococcus epidermidis (2 cases), and Streptococcus haemolyticus (1 case). Some pathogens were likely missed due to prior antibiotic use and fastidious growth requirements. Physicians adjusted treatments based on mNGS pathogen detection for culture-negative patients. Empirical therapy continued for patients with negative results until more diagnostic information was available. Conclusions: mNGS detects post-neurosurgery CNS infections, especially hard-to-cultivate microorganisms. While mNGS has advantages, traditional culture's higher positive predictive value confirms infections and remains indispensable. Combining mNGS with traditional methods provides a comprehensive diagnostic strategy, aiding physicians in accurately identifying infections, reducing misdiagnosis, and offering personalized treatment plans to improve outcomes and quality of life.